PELAKSANAAN EVALUASI AFEKTIF PADA MATA PELAJARAN PAI DI SMA NEGERI 2 RAMBATAN - Yeni Eka Putri (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
The study was purposed at explaining the affective evaluation and the obtacle on Islamic Education in State High School 2 Rambatan. This study used qualitative research method by applying observation, interview and documentation. Data were analyzed by using triangulation. The result of the study showed that the affective evaluation on Islamic Education got problem on conceptual and operational. The conceptual problem was difficult on applying the guidelines on the affective evaluation domain of the government and the Ministry of Religious Affairs. For the operational issue that the affective evaluation needs a lot of time, it pertains to feelings of students, and no cooperation in affective evaluation.Keywords: Affective Evaluation, Islamic Education, High School, Rambatan